Poultry Farming and Its Prospects for Development - Ibragimova, Orzigul (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2026)
Poultry farming has emerged as one of the most dynamic and rapidly developing branches of the global agricultural sector, playing a crucial role in ensuring food security, improving nutritional standards, and supporting rural economic development. Due to its relatively short production cycle, high feed conversion efficiency, and adaptability to various climatic and economic conditions, poultry production has become a strategic component of modern agribusiness systems. This article provides a comprehensive analysis of poultry farming as an agricultural activity and explores its future development prospects from economic, technological, environmental, and social perspectives. Special attention is given to the role of poultry farming in developing countries, including its contribution to employment generation, income diversification, and sustainable agriculture. The study also examines contemporary challenges such as disease control, feed resource limitations, environmental impacts, and market volatility, while highlighting innovative solutions based on technological advancement, genetic improvement, digitalization, and policy support. The findings suggest that poultry farming has significant growth potential if supported by scientific management, modern technologies, and integrated development strategies aligned with sustainability principles.